Bank Rating Gaps as Proxies for Systemic Risk - Wang, Lu (International Journal of Accounting and Financial Reporting, 2022)
Banks receive two types of ratings from major rating agencies: an “all-in” and a “stand-alone” rating. This paper investigates whether rating gaps between all-in ratings and stand-alone ratings could serve as a useful measure for the systemic risk of banks. Using US data from 1994 to 2007, the link between the rating gaps and a quantitative systemic risk measure, Co-independent Value at Risk (CoVar), is examined. The conclusion is that rating gaps are good proxies for systemic risk of large banks.